2015
DOI: 10.1068/p7823
|View full text |Cite
|
Sign up to set email alerts
|

Eye Shape Illusions Induced by Eyebrow Positions

Abstract: We investigated whether the position of the eyebrows influences the perceived shape of the eyes by employing psychophysical measurements. Experiment 1 used arched and straight eyebrows at five different inclinations as stimuli and measured the perceived inclination of the eyes. The results demonstrated that the eyes are perceived to be somewhat inclined in the same direction as the eyebrows. Experiment 2 measured the perceived eye size by manipulating the distance between the eyes and the eyebrows and the curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…One tendency is assimilative: Geometric illusions in body parts tend to induce illusions of assimilation instead of contrast. And Morikawa also observed that in the human face and body, the visual property of a smaller region can spread to larger adjacent areas, a phenomenon that he called “visual echo illusion.” These tendencies of biological illusion have been confirmed by some other studies (Matsushita et al., 2015; Morikawa, 2017). Indeed, the present study’s results seem to accord with the theory of biological illusion.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…One tendency is assimilative: Geometric illusions in body parts tend to induce illusions of assimilation instead of contrast. And Morikawa also observed that in the human face and body, the visual property of a smaller region can spread to larger adjacent areas, a phenomenon that he called “visual echo illusion.” These tendencies of biological illusion have been confirmed by some other studies (Matsushita et al., 2015; Morikawa, 2017). Indeed, the present study’s results seem to accord with the theory of biological illusion.…”
Section: Discussionsupporting
confidence: 86%
“…Face perception and lightness illusion (e.g., lightness perception is affected by the lightness of adjacent areas) have been investigated separately by numerous studies (Adelson, 2000; Tanaka & Farah, 1993) and are already established as different research fields with very little relationship. In addition, in recent years, perceptual effects of cosmetics have begun to draw attention as a promising new field of perceptual study (Matsushita, Morikawa, Mitsuzane, & Yamanami, 2015; Morikawa, Matsushita, Tomita, & Yamanami, 2015). However, very few studies, if any, have tackled the intersection of these three fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 The shortened distance between the eyebrow and eye is reported to increase the illusion of a larger eye. 25 Hence, the visually perceived dimension and aesthetics of the eye are further influenced by the relative proportions of the eyebrow–eye anatomical unit. 19 In this study, the vertical ratio of the actual eye fissure in the eyebrow–eye unit was significantly increased by 34.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The eyebrow plays a significant role in communication. 1 It conveys a wide range of expressions, such as sadness, anger, satisfaction, and joy. 2 Since the beginning of human civilization, it has been recognized as a key element in facial aesthetics.…”
Section: Introductionmentioning
confidence: 99%